(untitled) (Dandao Xuebao/Journal of Ballistics, 2023)
In order to ensure the uniform distribution of charge temperature field,it usually takes a long time for the charge to reach the thermal equilibrium state. To save the thermal equilibrium time,the heat transfer model of gun charge was established using the porous medium heat transfer theory. The finite volume method was used to discrete the mathematical model,and the corresponding difference calculation scheme was obtained. The temperature field and thermal equilibrium process of various caliber charges were simulated under different initial conditions. The theoretical calculation results were compared with the test data. The result shows that the theoretical model can correctly reflect the temperature change law of propellant charge,and the method has certain popularization and application value.